Intercultural communication for Christian ministry - Tucker, Frank (S.l. : Create Space, 2013)
This book is the most comprehensive work on intercultural communication theory and practice for cross-cultural Christian workers since the 1991 publication of David Hesselgrave$1 (Bs 'Communicating Christ Cross-Culturally: An Introduction to Missionary Communication'. It is written for the serious reader in Christian cross-cultural ministry and for graduate and postgraduate study. It considers significant developments in the electronic media such as the Internet, smart phone and other electronic resources. Thinking styles, psychology of art, ethnomusic, ethnodrama and methods of oral communication are included. Gender issues and the importance of personal relationships as a context for Christian ministry are explored as well as ethical issues in communication and issues in communicating with oral-aural people, shame-honour and fear-power cultures. It seeks to be culturally inclusive although it reflects the writer's culture of origin. The use of case histories and critical incidents are used to illustrate the text and ground the theory in reality.A companion website is provided for digital resources: video clips, ethnomusic, ethnodrama, visual arts, case histories, case studies and learning facilitator resources.s
Keywords: Intercultural communication -- religious aspects -- Christianity; Intercultural communication -- missions